2002
DOI: 10.1016/s0014-5793(02)03623-2
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's tyrosine kinase targets NF‐κB to the bcl‐x promoter via a mechanism involving phospholipase C‐γ2 following B cell antigen receptor engagement

Abstract: Disruption of Bruton's tyrosine kinase (BTK) function leads to x-linked immunode¢ciency (xid) in mice. BTKde¢cient (btk 3 3/3 3 ) B cells are defective for survival. Prior studies show that BTK is required for the induction of Bcl-x L following B cell antigen receptor (BCR) engagement. However, the mechanism underlying Bcl-x L induction in response to BCR ligation remains unresolved. We now demonstrate that BTK regulates bcl-x expression by transcriptional control in response to BCR engagement. BTK targets nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Btk has been shown to couple IB kinase, IB␣, and NF-B to the BCR, linking these key pathways (30); additionally, BTK directly regulates bcl-x expression by transcriptional control in response to BCR engagement (31).…”
Section: Resultsmentioning
confidence: 99%
“…Btk has been shown to couple IB kinase, IB␣, and NF-B to the BCR, linking these key pathways (30); additionally, BTK directly regulates bcl-x expression by transcriptional control in response to BCR engagement (31).…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, deletion of I B kinase results in a reduction of the mature FoB cell compartment (31,32). We have also shown that the transcription factor NF-B up-regulates the antiapoptotic protein Bcl-x L in response to BCR cross-linking in a BTK/PLC-␥2-dependent manner (33). Moreover, BCR-induced NF-B activation proceeds via protein kinase C␤ (PKC␤) (34 -36).…”
mentioning
confidence: 75%
“…It was recently proposed that DAG-dependent activation of conventional PKC␤ initiates a survival, but not a differentiation, program in response to BCR cross-linking through the activation of NF-B and induction of Bcl-x L (33,36). Thus, DAG at least in part may regulate T2 B cell survival via activation of the PKC pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous gene targeting experiments have demonstrated that signals transduced via BCR promote survival of quiescent mature B cells (Lam et al, 1997). Other studies have demonstrated that Btk is required for the induction of the antiapoptosis Bcl-2 family member, Bcl-xL, via the transcription factor NF-kB in B cells (Petro et al, 2002). It is therefore likely that p85a and Btk participate in the formation of the multi-component B-cell signalosome complexes which are required for the expression of the survival protein Bcl-xL following BCR stimulation, and pertubation of this B-cell signalling axis contributes to defective Bcl-xL expression and thus compromised survival of B cells.…”
Section: Discussionmentioning
confidence: 99%